Psychological predictors of future dangerous behavior among probationers: evidence from judicial bureaus in four provinces in China - Tang, Ling; Xu, Tun; Ma, Junming (Frontiers in Psychology, 2025)
IntroductionThe psychological mechanisms of future dangerous behaviors among probationers may be influenced by multiple factors. This study aims to explore the impact of relative deprivation on probationers’ future dangerous behaviors, with a focus on the mediating role of negative coping styles and the moderating effect of self-esteem on this pathway.MethodsA survey was conducted among 1,023 probationers from 48 judicial offices across four provinces in China. Data were collected using the Future Dangerous Behaviors Questionnaire (FDQ), Relative Deprivation Questionnaire (RDQ), Coping Style Questionnaire (CSQ), and Self-Esteem Scale (SES). The moderated mediation model was tested using SPSS PROCESS macro 3.3 software, with negative coping styles as the mediator and self-esteem as the moderator, while controlling for age, gender, education, crime type, sentencing term, and residency status.ResultsRelative deprivation was a significant predictor of probationers’ future dangerous behaviors. Negative coping styles partially mediated the relationship between relative deprivation and future dangerous behaviors, while self-esteem negatively moderated both the direct effect of relative deprivation on future dangerous behaviors and the mediating effect of negative coping styles.ConclusionThis study demonstrates the pivotal roles of subjective perception (relative deprivation), psychological mechanisms (negative coping styles), and personal resources (self-esteem) in shaping probationers’ future dangerous behaviors. Therefore, judicial officials should integrate community-based strategies to enhance probationers’ adaptive coping skills and improve their self-esteem, thereby reducing the likelihood of further dangerous behaviors and promoting successful reintegration into society.